1992
DOI: 10.1002/aja.1001940307
|View full text |Cite
|
Sign up to set email alerts
|

Id expression during mouse development: A role in morphogenesis

Abstract: We have characterized the spatial and temporal pattern of Id transcription during mouse embryogenesis. The Id gene encodes a helix-loophelix (HLH) protein which can heterodimerize with the ubiquitously expressed HLH protein products of the E2A gene, and prevent them from binding DNA either alone or as a heterodimer with tissue specific HLH transcription factors such as the muscle determination gene, MyoDl (Benezra et al., 1990 Cell 61:49-59). SinceId has been shown to be down-regulated during induced differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

1995
1995
1997
1997

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 40 publications
3
47
0
Order By: Relevance
“…From the initial expression analysis of M-twist (Wolf et al, 1991), it was concluded that the expression pattern is reminiscent to that of Id1 and Msxl, both of which are inhibitors of differentiation (Sassoon, 1993;Wang et al, 1992;Song et al, 1992). This more detailed investigation of M-twist expression confirms this assumption for some areas like the limb bud and the developing heart valves, where all three genes are expressed, and the somites, where Id1 and M-twist are colocalized .…”
Section: -Dsupporting
confidence: 60%
“…From the initial expression analysis of M-twist (Wolf et al, 1991), it was concluded that the expression pattern is reminiscent to that of Id1 and Msxl, both of which are inhibitors of differentiation (Sassoon, 1993;Wang et al, 1992;Song et al, 1992). This more detailed investigation of M-twist expression confirms this assumption for some areas like the limb bud and the developing heart valves, where all three genes are expressed, and the somites, where Id1 and M-twist are colocalized .…”
Section: -Dsupporting
confidence: 60%
“…The overall postgastrulational expression pattern of Id genes described in this study is as follows: Id1 (Wang et al, 1992;Duncan et al, 1992;Evans and O'Brien, 1993; this work), Id2 and Id3 are expressed in multiple tissues, and the expression patterns among them exhibit extensive overlap ( Fig. 1.1-4).…”
Section: Resultsmentioning
confidence: 99%
“…During axial skeleton development, Id1 (Wang et al, 1992;Evans and OBrien, 1993; this work), Id2, and Id3 signals are first observed in the 10.5 dpc somites. The somitic expression of these Id genes is mainly located in the sclerotome, and very weak signals appear in the dermatome.…”
Section: Expression In Developing Cartilage and Bonementioning
confidence: 99%
See 2 more Smart Citations